0434 A meta-analysis of occupational silica exposure and risk of autoimmune rheumatic diseases: does study quality matter?. (21st August 2017) - Kolstad, Henrik A; Beer, Christiane; Sherson, David; Troldborg, Anne; Nielsen, Berit Dalsgaard; Olesen, Anne Braae; Jacobsen, Gitte; Klaus, Søndergaard; Vivi, Schlünssen
Abstract : Objectives: Increased risks of rheumatoid arthritis, small vessel vasculitis, systemic lupus erythematosus, and systemic sclerosis have been observed following crystalline silica exposure. Our aims are to estimate pooled risk estimates and assess the impact of study quality. Methods: We followed the PRISMA criteria, identified 1162 articles, and included 21 studies that we classified according to eight quality parameters (high vs. low). We estimated pooled overall and disease specific odds ratios (ORs) with random effects meta-regressions. Results: We observed an increased overall OR of 2.3 (1.7–3.1, 21 studies) and for rheumatoid arthritis (OR 1.7, 95% CI 0.8–3.41, 6 studies), small vessel vasculitis (OR 2.4, 95% CI 1.2–4.7, 6 studies), systemic lupus erythematosus (OR 2.8, 95% CI 0.5–14.7, 3 studies), and systemic sclerosis (OR) 2.9, 1.7–4.9, 6 studies). The following high-quality characteristics were associated with decreased ORs: appropriate control group, high response rate, appropriate confounder control, independent exposure information, and many participants; and with increased ORs: quantitative or semi-quantitative exposure measure, hospital based diagnosis, and well-defined diagnostic criteria. Only the latter was statistically significant (p<0.05). When we consecutively excluded low quality studies, the overall OR value decreased to 1.3 (0.4–4.2, 3 studies) but this exercise was sensitive to the order. Egger's test of no small study effect was highly statistically significant (p<0.01). Conclusion: This review provides some evidence that crystalline silica is associated with systemic sclerosis, systemic lupus erythematosus, rheumatoid arthritis, and small vessel vasculitis. However, more high-quality studies are needed to confirm or refute if this represents causal associations.